3b-8/6=6-2(3b-2/3) Solve for b

2 Answers | Add Yours

crmhaske's profile pic

Posted on

The equation must be rearranged in order to group like terms (the b's and the constants):

`3b-8/6=6-2(3b-2/3)`

`3b-8/6=6-6b+4/3`

`3b+6b=6+4/3+8/6`

`9b=(36+8+8)/6`

`9b=52/6`

`b=52/54=26/27`

 

aruv's profile pic

Posted on

3b-8/6=6-2(3b-2/3)

You first apply BODMAS rule ,to simplify expression

`3b-8/6=6-2(3b-2/3)`

`3b-8/6=6-2xx3b+2xx2/3`

`3b-8/6=6-6b+4/3`

keep variable one side and constant other side

`3b+6b=6+4/3+8/6`

`9b=(6xx6+4xx2+8)/6`

`9b=(36+8+8)/6`

`9b=52/6`

`9b=26/3`

`b=26/(9xx3)`

`b=26/27`

We’ve answered 320,140 questions. We can answer yours, too.

Ask a question